Analysis of Business Model Canvas on Rock Hotel Using Blue Ocean Strategy - Herdito, Vido (Jurnal Ilmiah Mahasiswa FEB, 2018)
The Objective of this research is to analyse existing business model of Rock Hotel by using Business Model Canvas method and formulate new business model by utilising Blue Ocean Strategy’s four actions framwork (eliminate, reduce, create, raise). This study used descriptive qualitative method and collected data through interviews, observation, and documentation. The finding shows that Rock Hotel is currently in the red ocean condition. Rock Hotel needs to combine Business Model Canvas with Blue Ocean Strategy’s four action framework (eliminate, reduce, create, raise) to create strategic position in the industry. Rock Hotel as business budget hotel can provide family values which consist of business and family traveler and new costumer segments which consist of small, medium and startup company as their value innovation of value proposition.KEYWORDS: strategic analysis, business model canvas, blue ocean strategy, four actions framework, value innovation.